Deciphering the role of dimer interface in intrinsic dynamics and allosteric pathways underlying the functional transformation of DNMT3A - Liang, Zhongjie; Hu, Junchi; Yan, Wenying; Jiang, Hualiang; Hu, Guang; Luo, Cheng (Biochimica et biophysica acta, 2018)
DNMT3A, as de novo DNA methyltransferase, is essential for regulating gene expression through cellular development and differentiation. The functions of DNMT3A rely on its oligomeric states and allosteric regulations between its catalytic domain and binding partners. Despite recent resolution of autoinhibitory and active DNMT3A/3L crystal structures, the mechanism of their functional motions and interdomain allostery in regulating the activity remains to be established. The hybrid approach, comprising Elastic Network Models coupled with information theory, Protein Structure Network, and sequence evolution analysis was employed to investigate intrinsic dynamics and allosteric properties of DNMT3A resolved in autoinhibitory and active states. The conformational transition between two states is characterized by global motions, and the homo-dimer displays the similar dynamic properties as tetramer, acting as the basic functional unit. The hinge residues with restricted fluctuations are clustered at the dimer interface, which are predicted to enjoy remarkably efficient signal transduction properties. The allosteric pathways through the dimer interface are achieved by a cascade of interactions predominantly involving conserved and co-evolved residues. Our results suggest that structural topology coupled with global motions indicates the structural origin of the functional transformation of DNMT3A. The comprehensive analysis further highlights the pivotal role of the dimer interface of DNMT3A both in defining the quaternary structure dynamics and establishing interdomain communications. Understanding the global motions of DNMT3As not only provides mechanical insights into the functions of such molecular machines, but also reveals the mediators that determine their allosteric regulations. [Display omitted] •First insights into the intrinsic dynamics of DNMT3A in autoinhibitory and active states•Dimer interfaces in both states dictate allosteric communications•Network and evolutionary analysis highlights key residues in protein dynamics